The impact of 5-flurouracil on white matter tracts and possible protection by fluoxetine or indomethacin administration: in vivo and in vitro study - Al-Bayti, Ayoub Ali Hussein (2017)
Background: Long term cognitive impairment has been found in significant numbers of patients treated with chemotherapy. Both patient and animal studies have shown that white matter (WMT) integrity is affected by chemotherapy. This indicates that these changes are a possible cause of the deterioration in cognition. However very little is known around the mechanism behind the changes in WMT or the types of cells that are affected. In the CNS, proliferating precursor and stem cells appear to be particularly susceptible to chemotherapy. Reduced proliferation of oligodendrocyte precursors (OPCs), which are required for the maintenance of myelin sheaths, may lead to de-myelination within WMTs. In addition to direct effects on proliferating cells, chemotherapy induced inflammation may be involved in the long term effects of this treatment and prevent re-myelination. These affects could contribute to the cognitive decline experienced by patients after chemotherapy treatment. Recently, work in my laboratory has found that administration of antidepressant or anti-inflammatory drugs is neuroprotective against the cellular and behavioural effects of cytotoxic agents in the hippocampus. Thus, examples of these classes of drug were used to investigate their protective abilities in WMTs. Objectives: The studies in the present thesis used an in vivo rat model to evaluate the impact of acute and chronic systemic 5-Fluorouracil (5-FU) treatment on myelin integrity and OPCs proliferation in the optic nerve (ON) and corpus callosum (CC). The project also investigated whether 5-FU induced inflammation or DNA damage in these tissues. Additionally, an in vitro system was used to test the direct effects of 5-FU on the proliferation and survival of MO3.13 (OPCs); C6 (astrocytes), BV-2 (microglia) and HBMECs (endothelial) cells. Interactions between OPCs and these other cell types, when treated with chemotherapy, was investigated by co-cultures either when cells were in contact or separated by a porous membrane. Further studies investigated the potential protective effects of the antidepressant fluoxetine (FLX) and the anti-inflammatory drug indomethacin (INDO) when co-administered with 5-FU. Methods: Adult male rats were either acutely (single dose) or chronically (6 doses over 2 weeks) administrated 5-FU. Some groups were co-treated with either FLX or INDO administered via their drinking water prior to and during chemotherapy. Cell proliferation (Ki67), OPCs (NG2), microglia (Iba-1), inflammation (COX-2) and DNA damage (γ-H2AX) were quantified in both ON and CC by immunohistochemistry. Transmission electron microscopy (TEM) and electrophysiology were used to measuring the density of myelinated axons, myelin thickness and the compound action potential (CAP) 7 days after treatments. The in vitro study, tested cell viability after treatment with 5-FU with or without the presence of FLX or INDO. This was followed by co-cultures of OPCs with different cell types to determine if co-culture would affect OPCs viability during chemotherapy. Conditioned media, co-cultures allowing cell to cell contact and co-cultures in which the cell types were separated by a porous membrane were used. OPC viability after 5-FU exposure was tested under these conditions together with the presence of FLX or INDO. The gap junction (GJ) protein connexin47 was stained for and dye transfer was used to determine if functional GJ were present between cell types. Treatment with the GJ blocker CBX was used to determine the effect of functional GJ on viability. An ELISA was used to detect whether microglia release TNF-α when treated with 5-FU. Results: Rats treated with 5-FU showed a decrease in cell proliferation and the numbers of both OPCs and microglia in both ON and CC. Both single and multiple injections of 5-FU produced a significant increase in the numbers of COX-2 positive cells 24 hours and one week after treatment. DNA damage was found one week after 5-FU injection. TEM showed no change in the density of myelinated axons but a decrease in myelin thickness in the ON and CC. However there is no significant difference in the CAP of ON with 5-FU treatment. This study has shown that the viability of all cell types was reduced by 5-FU with the most sensitive cells being microglia followed by OPCs. FLX or INDO co-administration before, during and after chemotherapy injections reduced and counteracted the adverse effects of 5-FU treatment in vivo. However treatment of OPCs in vitro with FLX or INDO was unsuccessful in protecting OPCs. Co-culture of OPCs with either astrocytes or endothelial cells protected OPCs from 5-FU treatment if cell contact was allowed between the different cell types. GJ proteins were detected in all cell types and dye transfer showed that functional GJ existed. Blocking GJ in co-cultures reduced the protection to OPCs from 5-FU. Chemotherapy was shown to activate microglia and increase TNF-α production which in turn inhibited OPCs survival. FLX and INDO treatment inhibited microglial activity after 5-FU treatment. Conclusions: Chemotherapy caused inflammation and DNA damage in WMTs, and reduced cell proliferation and decreased the number of OPCs in ON and CC. These changes were associated with a reduction in myelin thickness. The deleterious effects of chemotherapy were prevented by prior FLX or INDO treatment. In vitro studies showed activation of microglia and release of TNF-α. As inflammation is one of the main effects of chemotherapy on WMTs its reduction by FLX or INDO is likely to have beneficial effects of the cognitive impairment experienced by patients. INDO has been shown to have anti-cancer effects and to synergise with existing cancer treatments and its use may benefit patients being treated with chemotherapy.